Development Plan of Private Vocational Competency Development Training Institutes - Sung-Sik Yoo, Jun-Hyeok Seo, Soo-Yong Park, Dong-Hyung Lee (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Until now, private vocational competency development training has been continuously expanded quantitatively, but it shows limitations in qualitative growth. Although private vocational training institutions have been greatly expanded in line with the entry of knowledge-based economies, industrial structure advancement, and the advent of the Fourth Industrial Revolution, it is still insufficient in terms of quality of training, and training high-skilled workers. Therefore, private vocational training institutions need to respond quickly to changes in the training environment, such as the economic and social environment, the industrial sites, and the vocational training system. This study aims to derive a plan to enhance the competitiveness of private institutions by specifically and accurately grasping the reality of private vocational competency development training, predicting future changes in the training, and analyzing factors that hinder the training operation effects. To this end, the problems of the current vocational competency development project are identified based on existing literature, research results and a survey conducted on related workers, the most urgent and important enhanced measures are drawn using IPA techniques. The results of this study are summarized as follows. First, the strategy with high importance and urgency is to apply the diverse and differentiated programs first than competitive institutions. Second, the strategy with high importance and low urgency is to thoroughly check the current situation and improve the cost system. Third, the strategy with low importance and urgency is to develop a program linked to the import business for the institution's independent survival in the long run. Fourth, the strategy with low importance and high urgency is to benchmark advanced foreign institutions to flexibly respond to various situations. This research is expected to contribute to strengthening their competitiveness by establishing suitable operational strategies for private vocational competency development institutions.